Towards the end of the morning - Frayn, Michael (Collins, 1967)
Michael Frayn's classic is set in the crossword and nature notes department of an obscure national newspaper during the declining years of Fleet Street, where John Dyson dreams wistfully of fame and the gentlemanly life - until one day his great chance of glory at last arrives.